IDENTIFYING EARLY READING COMPETENCE IN ELEMENTARY SCHOOL STUDENTS (International Conference on Elementary Education, 2018)
Early reading competence is an early reading competence given to grade first students to enable students to read and develop language knowledge and language skills to face the next class. The purpose of this research is to identify early reading competence of the first-grade students of Elementary School. The research was performed in July 2018. The method used in this research was a quantitative descriptive method. The subject of this research were grade first students in SDN 177 Pekanbaru which amounted to 28 people. Data analysis technique used in this research is the descriptive analysis that describes data result of observation of early reading competence of the first-grade student in elementary school. Based on the research found as many as 35.71% had been able to read smoothly, 64.29% of students were already of early reading competence stage and 39.29% of students were unable to read. Early reading competence of the grade first elementary school where 10 students have mastered all indicators of early reading competence, 7 students have already mastered the indicator of early reading competence and 11 students are unable to master the indicators of early reading competence.